(untitled) (Materiali di Estetica. Terza serie, 2022)
The aim of this paper is to analyse the numerous metaphors that Plato employs in his Republic to symbolise the ignorance, the immorality, and the political inadequacy of the “multitude”, in other words the people who live in a democracy. Plato’s symbols highlight the negativity – illustrated in other dialogues as well – of the Athenian demos in order to suggest the only political role that people must play: becoming subjects of the “divine” philosophers in the perfect city described in the Republic. Only by relying on philosophers’ guidance can the multitude be saved from itself: through one of the most recurrent symbols of the demos, the animal, Plato reveals his scepticism towards democracy and his preference for an oligarchy ruled by philosophers.